Cloud Computing Web-Based Dynamic IT Services - Baun, Christian; Kunze, Marcel; Nimis, Jens; Tai, Stefan (Springer eBooks., 2011)
Cloud computing is a buzz-word in today?s information technology (IT) that nobody can escape. But what is really behind it? There are many interpretations of this term, but no standardized or even uniform definition. Instead, as a result of the multi-faceted viewpoints and the diverse interests expressed by the various stakeholders, cloud computing is perceived as a rather fuzzy concept. With this book, the authors deliver an overview of cloud computing architecture, services, and applications. Their aim is to bring readers up to date on this technology and thus to provide a common basis for discussion, new research, and novel application scenarios. They first introduce the foundation of cloud computing with its basic technologies, such as virtualization and Web services. After that they discuss the cloud architecture and its service modules. The following chapters then cover selected commercial cloud offerings (including Amazon Web Services and Google App Engine) and management tools, and present current related open-source developments (including Hadoop, Eucalyptus, and Open CirrusTM). Next, economic considerations (cost and business models) are discussed, and an evaluation of the cloud market situation is given. Finally, the appendix contains some practical examples of how to use cloud resources or cloud applications, and a glossary provides concise definitions of key terms. The authors? presentation does not require in-depth technical knowledge. It is equally intended as an introduction for students in software engineering, web technologies, or business development, for professional software developers or system architects, and for future-oriented decision-makers like top executives and managers.